Jihad as an essential principle of human life an understanding from the Qur’anic perspective - Khan, Israr Ahmad (International Islamic University Malaysia, 2011)
Many a Qur’anic concept has been misunderstood and misinterpreted by both protagonists and antagonists. JihÉd is one such Qur’anic term. Today its meaning, purpose, and application appear confusing. The most popular import of this term is war against the enemies of Islam. Does this meaning of jihÉd commensurate with its Qur’anic usage? Or have Muslim scholars and commentators of the Qur’an imposed their own idea of jihÉd in the minds of the people? To resolve this entangled and misunderstood Qur’anic usage of jihad in an objective manner is a big challenge to the Muslim scholars of the post-modern era. The word jihad has occurred in the Qur’an forty one times, eleven times in Makkan revelations and the remaining thirty times in Madinan revelations. It has been used in both noun and verb forms. In order to understand, and interpret the concept of jihad in the Qur’an, one has to read it within the contexts it has occurred. To read a statement in isolation of its context is in sheer contrast with universally established rule of justice. If the word jihad in the Qur’an is read and deliberated over within the given context, it may appear that jihad is not an act of Islamic life like solah, zakah, hajj, nikah etc but rather it is an underlying principle of life to be applied in every walk of life. It is like the other Qur’anic principles of life such as ihsan, taqwa, ‘adl etc. The word jihÉd denotes doing the best everywhere, whether in devotional matter, social life, economic undertaking, political struggle, cultural activity, educational endeavor, or military expedition. It is suggested here that all the forty one verses where the word jihad has occurred in the Qur’an should be interpreted by applying coherent methodology. The writer of this paper hereby proposes to do his part of jihad with intellectual honesty to interpret the word jihad as used in the Qur’an. For that purpose, he will, wherever it is possible, refer to scholars’ views and evaluate them critically so as to unfold the truth concerning jihad in the Qur’an.